(untitled) (Research, Society and Development, 2021)
Women over the years face several physiological changes, related to the different phases of their life, such as menarche, pregnancy, or the last menstrual period. Climacteric is a process of transition from the reproductive to the non-reproductive phase, a spontaneous event, which according to the World Health Organization (WHO), occurs between 40 and 65 years of age for women and involves several aspects, such as: endocrine, functional, emotional and socio-cultural. This study aims to analyze the main impacts of climacteric on the quality of life of women living in a southwest city of Bahia. This is a study with a descriptive quantitative approach characterized as cross-sectional. The studied population was a group of 42 women aged between 40 and 65 years. A semi-structured questionnaire divided into two parts was used as a data collection instrument, the first focused on the identification of the socioeconomic profile and the second composed by questions of clinical approach on the climacteric. The results are indispensable to mood instability and as sleep changes as the main factors that interfere in the quality of life. The profile of the women interviewed shows a social change in relation to previous studies, as these are financial independence, take care of the body and had access to education. However, there is still a negligence regarding the care that must be developed during this period.